Особенности поведения поляков и украинцев в ситуациях конфликта (На основе применения метода анкеты-конфликта) - Грушевская, С. (Социология: теория, методы, маркетинг, 2000)
The questionnaire-conflict was aimed to present general characteristic features of behavior in conflict situations among representatives of different societies: Polish and Ukrainian; that means to analyze and assess conflicts at macro level. The data related to the frequency of conflict outbreaks were analyzed according to the following kinds of conflicts: inner, interpersonal and social. The results of the polls conducted in Poland and Ukraine, as well as comparative polls held in both countries are presented.